Pengaruh Content Marketing, Sales Promotion, Personal Selling Dan Brand Image Terhadap Minat Beli Pada CV Laditri Karya - Tia Hardiyanah; Rini Hidayati; Ananta Hagabean Nasution; Muslikh Muslikh; Siti Marhamah (Journal of Accounting, Management, and Economics Research (JAMER), 2023)
This research was conducted with the aim of testing the effect of content marketing, sales promotion, personal selling and brand image on buying interest in CV Laditri Karya. The sample used in the study was 100 followers of the @laditrikarya Instagram account with a survey method in the form of a questionnaire which was processed using SPSS 24. The results of this study stated that: (1) content marketing had no significant effect on buying interest. (2) sales promotion has a positive and significant effect on buying interest. (3) personal selling has no significant effect on buying interest. (4) brand image has a positive and significant effect on buying interest. (5) content marketing, sales promotion, personal selling and brand image influence buying interest simultaneously